Occupational Exposure of Firefighters in Non-fire Settings - Slezakova, K. (2022)
Freshwater pollution is a huge concern. A study aiming to evaluate physico-chemical characteristics, microbiota, occurrence of two groups of persistent environmental pollutants with similar chemical properties (polycyclic aromatic hydrocarbons- PAHs and microplastics - MPs) in Alqueva's surface water was performed during 2021.